Empowering Learning: Elevating Arabic Writing Skill Proficiency Through Team Assisted Individualization for Grade X Students - Amrullah, M. Kholis; Riwanda, Agus; Islamy, M. Irfan (Universitas Islam Negeri Raden Intan Lampung, 2024)
The differences in Arabic language proficiency in MAN 4 Hulu Sungai Tengah (HST) were attributed to students' diverse educational backgrounds and experiences. Students who received education in pesantren or boarding schools generally tend to exhibit better mastery of the Arabic language compared to those from MTs and SMP. This variability in proficiency posed a challenge for teachers in managing instruction and achieving the Learning Objective Achievement Criteria (LOAC). This classroom action research employed the Team Assisted Individualization (TAI) method to enhance students’ skills. The outcomes of cycle 1 reveal the class average scores for each LO as follows: LO1: 95, LO2: 82, and LO3: 68.25. It was known that students had not met the LOAC for LO3, which requires a minimum score of 70. Cycle 2 entails adjustments to the TAI method by incorporating comic media, sequential imagery, and the implementation of a reward system. The evaluation results for LO3 in cycle 2 showcase significant progress, with all students achieving or surpassing the LOAC. The average score increased from 68.25 to 79. By implementing adaptations involving rewards, comic media, and serial imagery, the Team Assisted Individualization method proved effective in enhancing skills of Grade X students at MAN 4 Hulu Sungai Tengah.